Adjustable chiral self-sorting and self-discriminating behaviour between diamond-like Tröger's base-linked cryptands. Issue 56 (25th June 2019) - Chen, Yuan; Qian, Cheng; Zhao, Qian; Cheng, Ming; Dong, Xinran; Zhao, Yue; Jiang, Juli; Wang, Leyong
Abstract : Adjustable chiral self-sorting and self-discriminating behaviour between diamond-like Tröger's base-linked cryptands was reported, which could be regulated by external stimuli easily. Abstract : Two isomers of Tröger's base-linked cryptands5a and5b were synthesized, and both of them have two chiral N-centers, exhibiting rare diamond-like scaffolds. Particularly, when growing from the solution of rac -5a, a single enantiomer R N R N -5a was found in the crystal cell, revealing chiral self-sorting behaviour. However, when adding CF3 COOH to protonate Tröger's base in the solution of rac -5a, two enantiomers were both formed in pairs in the crystal cell, exhibiting chiral self-discriminating behaviour.